1999
DOI: 10.1002/(sici)1521-3803(19990101)43:1<22::aid-food22>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Essential amino acid composition and biological quality of yambean,Sphenostylis stenocarpa(Hochst ex A. Rich) Harms

Abstract: The essential amino acids and protein bioavailability of raw, roasted and pre-soaked, pressure cooked yambean were evaluated. Roasting caused decrease of 8% while soaking with pressure cooking caused decrease of 15-39% in the lysine composition of yambean. Rats fed raw, unprocessed bean diet showed overt signs of diarrhoea, poor protein utilization and hence poor growth. Processing considerably improved all growth indices--food conversion efficiency, protein efficiency ratio, digestibility, biological value, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As for the cause of diarrhoea and cramps, Asuzu and Undie1 concluded that increased peristaltic movement of the intestine together with quick passage of the intestinal content, which results from the stimulation of muscarine receptors, is the mechanism underlying diarrhoea. Published work on African yambeans has focused on their proximate composition, protein availability and functional properties and on the effects of modifying basic processing parameters such as soaking, dehulling and heat treatment 2–8. These include soaking in different media before cooking in water,9 though the serious problem of the unduly long cooking time was not the focus of that work.…”
Section: Introductionmentioning
confidence: 99%
“…As for the cause of diarrhoea and cramps, Asuzu and Undie1 concluded that increased peristaltic movement of the intestine together with quick passage of the intestinal content, which results from the stimulation of muscarine receptors, is the mechanism underlying diarrhoea. Published work on African yambeans has focused on their proximate composition, protein availability and functional properties and on the effects of modifying basic processing parameters such as soaking, dehulling and heat treatment 2–8. These include soaking in different media before cooking in water,9 though the serious problem of the unduly long cooking time was not the focus of that work.…”
Section: Introductionmentioning
confidence: 99%
“…While the mean feed intake (62.48–73.35) for all the diets is not significantly different ( P > 0.05), the mean feed conversion efficiency (0.51–0.88) of supplemented diets were significantly higher ( P < 0.05) than the mean feed conversion efficiency of −0.08 and −0.32 for animals fed the non‐supplemented and basal diet, respectively. The feed conversion efficiency indicates how well a food product is utilised in the body (Agunbiade & Longe, 1999). The results, as shown in Table 1 indicate that the supplemented diets, MG3, MG4, MS1, MS2, MS3 and MS4 were well utilised.…”
Section: Discussionmentioning
confidence: 99%
“…The carcass/body‐weight ratio is an indication of organ status in the test animal (Agunbiade & Longe, 1999; Sakanata et al. , 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations